Servitization by classification societies in times of COVID-19 - Ho, Charles Chee Yong (2021)
COVID-19 has affected many companies in more ways than one, ABS is no exception. However, this pandemic has offered ABS opportunities to further increase its inventory of services, by offering solutions to meet the newly brought about needs of its clients.